Design and Fabrication of Broadband Polymer Mode (De)Multiplexer Using a Direct Inscribing Method - Xiao Xu; Lin Ma; Chinami Marushima; Takaaki Ishigure; Zuyuan He (IEEE Photonics Journal, 2018)
We demonstrate the design and fabrication of a mode (de)multiplexer based on the tapered mode-selective coupler. The proposed device is directly inscribed in the substrate material by a needle-type liquid micro-dispenser and a three-axis robot stage using commercially available UV-curable resins. The fabricated mode (de)multiplexer has an excess loss less than 0.3 dB, a coupling ratio higher than 0.93, and an extinction ratio higher than 23 dB within a broadband of 100 nm around 1550 nm. The near field patterns of LP $_{11}$ mode at different wavelengths were successfully observed using an infrared charge-coupled-device camera. The fabrication tolerance on the spacing, core diameter deviation, and core circularity were investigated and the results imply that our fabrication process can satisfy the requirements on it. The proposed method is capable of fabricating functional devices for high-speed on-board optical interconnects.